"Can I Talk about That?" Factors Influencing Spiritual and Religious Identity Exploration in Public Higher Education. Issue 2 (3rd April 2017) - Durant, Tamara J.
Abstract: College students are increasingly interested in spiritual and religious identity exploration. Factors influencing such inquiry at public institutions of higher education include rational empiricism, cultural norms, and faculty and student affairs professionals' uncertainty about what is permissible, as well as their perceived level of preparation to guide such inquiry. Yet, students at public colleges and universities should be provided with opportunities to interrogate issues of purpose, identity, and meaning.